Stock Price Reactions Around Cum-Dividend Date in Indonesia Stock Exchange - Eka Lavista; Elok Sri Utami (STIE Malangkucecwara, 2017)
Purpose – This study is trying to examine whether there is significant stock prices and volume of shares traded on the cum-dividend date, the last day where shareholders will still be entitled to receive dividends. Design/methodology/approach – This study employs an event study methodology to test the hypotheses. The population of this study are all companies paying dividends continuously from 2014 to 2016 at Indonesia stock exchange. The sample consists of 118 companies. Abnormal returns are measured by deducting real return over expected return. The expected return is derived using the single index model. Findings – Employing the event study methodology, the study finds that there is positive significant abnormal returns on the cum-dividend date. There is also significant difference of abnormal returns and trading volume activity between cum-dividend date and after cum-dividend date. Research limitations/implications – This study does not examine the behavior of stock prices with-in industry in the manufacturing sector. As there are three different industries in the manufacturing sector, one industry may have unique characteristic or extreme behavior compared to the others. In addition, this study uses the Single Index Model in estimating expected return. The model is selected mainly due to simplicity reason. Practical implications – The findings reported in this study could benefit investors in understanding the behavior of stock prices around cum-dividend date and this could be used as an investment strategy. Investors may obtain significant positive abnormal returns by using the cum-dividend date event. Originality/value – There are many theories on dividend proposed by scholars. One of the theory suggests that dividend can be used as a signal about the quality of the firm. If the extent of dividend matters, the investor could use the dividend as their signal for investment in the capital market. This study could be the first in Indonesia setting that examines the price movement around cum-dividend date